Occurrence of Temnocephala (Platyhelminthes: Temnocephalida) in Immatures of Kempnyia reticulata (Enderlein) (Insecta: Plecoptera: Perlidae) - Avelino-Capistrano, Fernanda; Barbosa, Leandro Silva; Cunha, André Mallemont (EntomoBrasilis, 2013)
First register of Temnocephala (Platyhelminthes: Temnocephalida) in immature of Kempnyia reticulata (Enderlein) (Plecoptera: Perlidae). The insects were collected in rivers of Estação Biológica de Santa Lúcia, Santa Teresa, Espirito Santo, Brazil. Primeiro registro de Temnocephala (Platyhelminthes: Temnocephalida) em imaturos de Kempnyia reticulata (Enderlein) (Plecoptera: Perlidae). Resumo. Primeiro registro de Temnocephala (Platyhelminthes: Temnocephalida) em imaturos de Kempnyia reticulata (Enderlein) (Plecoptera: Perlidae). Os insetos foram coletados em um riacho da Estação Biológica de Santa Lúcia, Santa Teresa, Espírito Santo, Brasil.